2020
DOI: 10.1080/09538259.2020.1848624
|View full text |Cite
|
Sign up to set email alerts
|

What Does It Take to Be Top Women Economists? An Analysis Using Rankings in RePEc

Abstract: Women are substantially under-represented in the field of economics all around the world: their progress is slow and just few women reach top positions. From the 1980s, studies document the clear barriers and implicit biases in publishing, promotion, and tenure that women face to enter and to success in the field. The paper aims at contributing to this strand of literature proposing an analysis of gender differences in economics focusing on "excellence" in the profession and in the way the discipline is concei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Facing this, calculations of the likelihood of success and what trade-offs they need to make becomes a conscious or unconscious act in order to succeed. Many perceive they have a very low chance for a career pay-off in spite of an extremely high work effort (the latter also affected their ability to maintain a life outside academia), which is a belief supported by other studies (White, 2003;Zacchia, 2020). Because they observed that the same effort was not needed for male colleagues, the study participants concluded that their possibility for a successful career in the system was slim unless something within the organization would change to specifically address this bias.…”
Section: High Workload Limited Opportunity For Pay-offmentioning
confidence: 85%
“…Facing this, calculations of the likelihood of success and what trade-offs they need to make becomes a conscious or unconscious act in order to succeed. Many perceive they have a very low chance for a career pay-off in spite of an extremely high work effort (the latter also affected their ability to maintain a life outside academia), which is a belief supported by other studies (White, 2003;Zacchia, 2020). Because they observed that the same effort was not needed for male colleagues, the study participants concluded that their possibility for a successful career in the system was slim unless something within the organization would change to specifically address this bias.…”
Section: High Workload Limited Opportunity For Pay-offmentioning
confidence: 85%
“…Hengel (2018) finds that women experience longer turn-around times and more stringent writing requirements from journal reviewers. Zacchia (2020) shows that some of the ranking methodologies for top economists systematically disadvantage women. And Wu (2020) finds that women economists have been systematically trivialized or even sexualized in online forums.…”
Section: Some Backgroundmentioning
confidence: 99%
“…To mention just a few, citations are found to correlate with the number of authors, the year, language, and kind of publication, and the reputation of the journal (Laband, 2013); and at the author level, with academic seniority, field and degree of specialisation, and gender (Grossbard et al, 2020; Hengel & Moon, 2020). Yet, differently from other social scientists, economists often see citations as a measure of scientific quality : a rough proxy, perhaps, but generally an unbiased one (see Hamermesh, 2018; Zacchia, 2021). This assumption reflects a historical attitude in the natural sciences that, however, is increasingly challenged.…”
Section: Introductionmentioning
confidence: 99%
“…First, we consider both status and value homophily, operationalised through a rich set of connections among economists, whereas extant literature typically focuses on one set of links at a time. Second, while extant literature mostly focuses on coauthorship networks (or at most citation networks among journals), we focus on dyadic citations among authors, a currently understudied topic in economics, despite the economists' obsession with rankings and the use of citations to supposedly quantify excellence (Zacchia, 2021). 3 For a recent example of how this could happen without implying any bad faith, see for example Brancaccio (2022).…”
mentioning
confidence: 99%